Characterisation and application of carbon doped aluminium oxide optically stimulated luminescence dosimeter in megavoltage photon beams for radiotherapy / Fasihah Hanum Md Yusof - Fasihah Hanum , Md Yusof (2016)
Radiotherapy is long recognised as a method to treat cancer. In recent years, advanced radiotherapy techniques such as intensity modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) has been introduced. These techniques allows the delivery of escalated radiation dose with better target conformity, which leads to the needs of precise and accurate treatment verification to ensure the correct dose is being delivered to the target during radiotherapy. Besides the pre-treatment quality assurance, in-vivo dose verification may be needed. Optically stimulated luminescence dosimeter (OSLD) is a relatively new dosimeter which uses light photons to stimulate the release of dosimetric traps. This study covers the characterisation and application of the OSLD in selected radiotherapy techniques. The first part of this study investigated the physical characteristics of the OSLD for dosimetry under megavoltage photon beams. The OSLD were tested for different energies, repetition rates, field sizes, source to surface distances (SSD), and beam incident angles. The linearity, reproducibility, fading effect, signal depletion per readout and the effect of cumulative dose of the OSLD were also investigated. The OSLD demonstrated good linearity and reproducibility, stable after nine minutes post-irradiations, small signal depletion per readout (0.03%), small dependence of energy (≤5.23%), repetition rate (≤2.60%), SSD (≤2.34%), field size (≤5.23%) and angularity (≤3.50%). For practicality, detectors are often placed on the skin of patient for in-vivo dose measurement. In the second part of this study, the suitability of using the OSLD in measuring surface dose during radiotherapy was investigated. The water equivalent depth (WED) of the OSLD was first determined followed by comparisons of surface dose measured on a solid water phantom using the OSLD, which was benchmarked iv against measurements using the Markus ionization chamber and Gafchromic EBT3 film. The OSLD was also used to measure surface of a cohort of 10 patients undergoing conventional 3D conformal breast radiotherapy to evaluate its feasibility and accuracy in real clinical setup. The OSLD has a WED of 0.4 mm depth which consequently overestimated the surface dose by a factor of 2.37 for 6 MV and 2.01 for 10 MV photon beams, respectively. In the third part of the study, the OSLD was used for dosimetric verification of treatment plans namely 3D-CRT, IMRT and VMAT. Three plans were generate in 3D-CRT treatment planning which are single field, opposed fields and 4-fields. In IMRT and VMAT, two plans were generated simulating head and neck and prostate cases. The OSLD measurements were compared to TPS predicted dose. The uncertainty of the measurement was found to be within 3.16 ± 2.20% at the region where the dose is homogeneous. At the slight dose gradient region, the uncertainty was expected to be within 6.4 ± 4.2% and at regions where large dose gradients exist, the uncertainty was expected to increase to 9.0 ± 6%. In conclusion, the OSLD was found to be suitable to be used as a dosimeter for megavoltage photon beams. However, due to the finite size of the detector, the measurement uncertainties increase with the complexity of the treatment techniques.